β-Asarone Attenuates Aβ-Induced Neuronal Damage in PC12 Cells Overexpressing APPswe by Restoring Autophagic Flux - Li, Zhenwan; Ma, Jin; Kuang, Zhongsheng; Jiang, Yong (Frontiers in Pharmacology, 2021)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive memory damage and cognitive dysfunction. Studies have shown that defective autophagic flux is associated with neuronal dysfunction. Modulating autophagic activity represents a potential method of combating AD. In Chinese medicine, Acori Tatarinowii Rhizoma is used to treat dementia and amnesia. β-Asarone, an active component of this rhizome can protect PC12 cells from Aβ-induced injury and modulate expression of autophagy factors. However, its cytoprotective mechanisms have yet to be discerned. It is unclear whether β-asarone affects autophagic flux and, if it does, whether this effect can alleviate Aβ cell damage. In the present study, we constructed APPswe-overexpressing PC12 cell line as a cell model of Aβ-induced damage and assessed expression of autophagic flux-related proteins as well as the number and morphology of autophagosomes and autolysosomes. Our results show that β-asarone decreases the expression levels of beclin-1, p62, LC3-Ⅱ, and Aβ1-42. β-Asarone reduced the number of autophagosomes and increased the number of autolysosomes, as determined by confocal laser scanning microscopy and transmission electron microscopy. Our results suggest that β-asarone can protect PC12 cells from Aβ-induced damage by promoting autophagic flux, which may be achieved by enhancing autophagosome-lysosome fusion and/or lysosome function.